118k views
4 votes
Noah started to solve the equation –4.6p – 6.3p + 3.9 = –9.18 below. Combine like terms: –10.9p + 3.9 = –9.18 Apply the next steps to solve the equation. What is the solution? p =

User Twhb
by
5.6k points

2 Answers

7 votes

Answer: p=1.2

Explanation:

edge 2022

User Chuck Pinkert
by
5.7k points
5 votes

Answer:

The next steps are to:

1) subtract 3.9 from both sides

2) divide both sides by -10.9

3) p = 1.2

Explanation:

To solve a multi-step equation, you need to first combine like terms, which was done for your to get the equation: -10.9p + 3.9 = -9.18. At this point, you have a two-step equation where you need to use inverse (opposite) operations to isolate the variable. Whatever you do to one side of the equation, you do to the other:

1) -10.9p + 3.9 - 3.9 = -9.18 - 3.19 or -10.9p = -13.08

2) -10.9p/-10.9 = -13.08/-10.9

3) p = 1.2

User Sensei James
by
5.3k points